Gas Analysis of Carbon Oxidation in a Coin‐Type Direct Carbon Fuel Cell. Issue 4 (2nd May 2014) - Lee, C. G.; Pak, J.
Abstract Carbon oxidation behaviors were illuminated in terms of gas composition in a coin‐type direct carbon fuel cell. The main gas species in the anode chamber at 850 °C was mostly carbon monoxide, which was generated from the chemical reaction of carbon and molten carbonates. The concentration of CO was reduced as time passed because the reactivity of carbonates was weakened. The open circuit voltage was directly dependent on the CO concentration. The gases in the anode chamber had a vertical concentration distribution; the highest CO and the lowest CO2 concentrations were observed near the electrode. However, the voltage in the polarization state was less dependent on the gas composition. A polarization state of 150 mA cm–2 allowed the oxidation of CO, resulting in an increased CO2 concentration near the electrode. The enlarged CO2 partial pressure facilitated CO generation through the recombination of carbonate ions (CO32–). Decreasing the temperature from 850 to 750 °C reduced the level of carbon monoxide at the anode. The presence of CO as a main component in the anode concludes that the oxidation of solid carbon takes place through the gasification of carbon to CO, then electrochemically to CO2.